The Role and Current Status of IFRS in the Completion of National Accounting Rules – Evidence from the Czech Republic. (4th May 2017) - Jindrichovska, Irena; Kubickova, Dana
Abstract: The aim of this paper is to characterize the extent to which International Financial Reporting Standards (IFRS) is used as a reference point for national accounting rules in the Czech Republic (CR) and what elements are incorporated in Czech Accounting Regulation, paying particular attention to the latest amendment to the Accounting Act (AA) based on the EU accounting Directive (2013/34/EU). Methods used include analysis of Ministry of Finance documents, interviews with the team members who participated in the new wording of the AA to adapt it to the EU Directive and comparison of current to existing IFRS reporting rules. The results confirm that IFRS implementation in the CR is determined by economic and institutional factors, a major part of which is played by foreign ownership of dominant Czech companies and their subordinate position as subsidiaries of foreign entities and the weak capital market. Implementation of elements of IFRS into Czech accounting standards is still only partial. This process takes place as an integral part of the process of reorientation of the entire economic system toward market principles, which includes the accounting system. Each change of the AA involves some elements of IFRS; however, between the two systems, there are still significant differences, the roots of which lie in a different (continental) model of accounting.